The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1088/1748-9326/aa9a78
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emissions effects of grid-scale electricity storage in a decarbonizing power system

Abstract: While grid-scale electricity storage (hereafter 'storage') could be crucial for deeply decarbonizing the electric power system, it would increase carbon dioxide (CO 2 ) emissions in current systems across the United States. To better understand how storage transitions from increasing to decreasing system CO 2 emissions, we quantify the effect of storage on operational CO 2 emissions as a power system decarbonizes under a moderate and strong CO 2 emission reduction target through 2045. Under each target, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…To co-optimize energy and reserves, we set regulation provision costs to $10, $6 and $4 ($ 2017 ) per megawatt-hour (MWh) for coal, NGCC and natural gas steam units, respectively. These costs capture variable operation and maintenance (VOM) and heat rate degradation costs incurred while providing reserves (Craig et al 2018b).…”
Section: Uced Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…To co-optimize energy and reserves, we set regulation provision costs to $10, $6 and $4 ($ 2017 ) per megawatt-hour (MWh) for coal, NGCC and natural gas steam units, respectively. These costs capture variable operation and maintenance (VOM) and heat rate degradation costs incurred while providing reserves (Craig et al 2018b).…”
Section: Uced Modelmentioning
confidence: 99%
“…To ensure system reliability against variable wind and solar generation and unexpected generator and transmission outages, as well as to approximate current reserve classes in ERCOT (Electric Reliability Council of Texas 2013), the UCED model includes three reserve classes: regulation, flexibility and contingency reserves (table 1) (SI.1). To capture greater reserve requirements at high wind and solar penetrations modeled here, the three reserve classes vary with load and wind and solar generation (Craig et al 2018b, Lew et al 2013. All reserve classes procure positive or up reserves, i.e.…”
Section: Uced Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Many existing studies of high wind and solar penetration assess the role of a couple of drivers in isolation or with a limited number of joint sensitivities (e.g. Fell and Linn 2013, Shearer et al 2014, Hirth 2015, MacDonald et al 2016, Craig et al 2018, Eshraghi et al 2018, Sepulveda et al 2018, as shown in SI appendix, table 1. Although these one-way sensitivities are valuable ceteris paribus experiments, they do not comprehensively assess the relative impact of a range of factors by jointly varying all drivers simultaneously.…”
Section: Introductionmentioning
confidence: 99%